Review on Wound Healing Activity of Ropana Taila (International Journal of Ayurveda and Pharma Research, 2022)
Wound is a break in the integrity of the skin or tissue often, which may be associated with disruption of the structures and functions. Wound healing is a complex series of events that begin when an individual gets affected by a wound. It is a mechanism whereby the body attempts to re-establish the integrity of the injured part. In modern biomedical sciences, research on wound healing agents is one of the developing areas. Natural compounds are used in skin wound care from many years due to their therapeutic activities, including anti-inflammatory, antimicrobial, and cell-stimulating properties. Various herbs, oils and natural resources have been described in Ayurveda with wound healing properties. Acharya Sushruta has explained many drugs and formulations for the treatment of Vrana (wound). One such formulation named Ropana Taila has been described in Sushsruta Samhita for Wound healing. The present review article is undertaken to discuss about the wound healing activity of Ropana Taila